Performance Measurement in Malaysia's Higher Education - Abdullah, Nur Anisah (2012)
As higher education utilises a considerable proportion of state spending, there is no escaping from close scrutiny on delivery and accountability. In facilitating the management of delivery of strategic outcomes, policies were adopted in ensuring higher education institutions were encouraged to measure performance. The Ministry of Higher Education (MOHE) implemented performance measurement and reporting systems for monitoring and evaluation in assessing the success of reform initiatives. By mid of 2012, public higher education institutions were expected conduct “self assessment and self-monitoring”. This paper puts a spotlight on performance measurement in higher education, discusses on the factors that shape performance measurement, the role of performance measurement, the types of indicators in use, and the use and usefulness of performance measurement information.